2020
DOI: 10.1177/1687814020971899
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic weight-based learning method for data detection in manufacturing

Abstract: In this study, a dynamic weight-based method combined with principal component analysis (PCA) was developed for the first time for detecting measurement data in manufacturing. This weight-based learning technique can learn and train the measurement data sequence to isolate incorrect data sources for achieving high accuracy when detecting various types of data. Research has revealed that unsuitable image or data features might cause poor performance in industrial inspections. In contrast to the previous inspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The hold-out procedure is employed by the SVM to determine the combination 24 : parameter C and radial basis function kernel parameter γ. The grid-search strategy is used to determine the two parameters in SVM.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hold-out procedure is employed by the SVM to determine the combination 24 : parameter C and radial basis function kernel parameter γ. The grid-search strategy is used to determine the two parameters in SVM.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The hold-out procedure is employed by the SVM to determine the combination 24 : parameter C and radial basis function kernel parameter g. The grid-search strategy is used to determine the two parameters in SVM. Wang et al 25 suggested trying exponentially growing sequencies of C (2 25 , 2 23 , ., 2 15 ) and g (2 215 , 2 213 , ., 2 3 ) to identify good input parameters when the grid-search method is adopted.…”
Section: Dynamic Stb Pca Methodsmentioning
confidence: 99%